Analysis of boundary condition effects on RC deep beams. (February 2020) - Arabzadeh, Abolfazl
Abstract: The end support of deep beams could have different effects on behavior of the beams. In this paper, experimental results of 43 deep beams with span -to -depth ratio of less than 3, different reinforcement arrangements and boundary conditions were investigated and discussed. Results indicated that, boundary conditions have important effects on ultimate loads, modes of failure and deflections; but crack formation and their patterns are almost the same irrespective of applied boundary conditions. Furthermore, the ultimate loads of the beams with fixed ends are 1.2–6 times of simply supported and continuous deep beams, depending on amount of main bottom and top reinforcements. Furthermore, in fixed -end deep beams, modes of failure and ultimate loads mostly depend on top main reinforcement. To examine the beams theoretically, available standards and published proposed methods were used. Results indicated that, none of existing methods is suitable for fixed- end deep beams, except proposed method. However, the methods proposed by ACI 318–14 and CIRIA Guide 2 yielded very conservative results for simply supported deep beams.